ANALISIS KEBUTUHAN AIR TANAMAN STRAWBERRY YANG DIBUDIDAYAKAN SECARA HIDROPONIK DI DALAM GREENHOUSE - I Made Purnadiyasa; I Wayan Tika; Ni Nyoman Sulastri (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2013)
The purpose of this study was to determine the pattern of water requirements for strawberry plant using hydroponic which was planted in the greenhouse, from transplanting to harvesting time. The materials used in this study were the strawberry seedlings, rice husk, NPK fertilizer and plastic polybag. The tools used were 4-way soil analyzer to measure soil pH, soil moisture, light intensity for soil, analytical balance, plastic tank that were used to store water, ruler and thermometer. Parameters observed were initial moisture content, the period of irrigation water supply, amount of water used by plants and irrigation water requirement. Based on the study which was conducted during the (i)high level is (57,66 ml/day), (ii)medium is (42,40 ml/day) and (iii)low is (30,06 ml/day) of soil moisture, it showed that crop water requirement depended on existing soil moisture. In addition, there was a trend that crop water requirement would increase as the increase of soil moisture. During low level of soil moisture (under the field capacity), the plant would experience difficulties in extracting water from soil. Conversely, during high level of soil moisture, water would easily be taken and plant water requirement would increase because of the increase of soil evaporation, especially during the initial stage of plant growth.